Holocaust Denial as Memory Criminal Law Seen Through the Nordic Lenses - Nuotio, Kimmo (Bergen Journal of Criminal Law & Criminal Justice, 2023)
Dealing with historical matters by means of law has become increasingly common. The matters, such as the Holocaust, that have merited the attention of legislatures are, however, exceptional. The painful memory of the horrible events has required a profound rethinking of the basic premises of political and legal life in Europe. When criminal law is being used to protect the memory of those facts and of the victims of the offences, we enter a level of highly symbolical legislation. In Continental Europe, the discussions concerning criminalisation of Holocaust denial emerged in the 1970’s, and in the 1990’s criminalising was already in full swing. The Nordic countries have been slow in joining such developments. In this paper we will try to bring the Nordic countries on this map by introducing some of these discussions to the Nordic scholarly audience, but also by reporting to the international scholarly community about some Nordic and particularly Finnish aspects of those subject issues. It is time for Nordic criminal law scholars to join these debates and to bring in viewpoints on the basis of Nordic criminal law and theorising. This article aims at contributing to such a discussion.